Advancements and trends in agricultural veterinary education research: a text mining and network analysis approach - Huang, Liang; Wu, Hairong; Peng, Juhua; Liu, Jinsi (Frontiers in Veterinary Science, 2026)
IntroductionWith the deepening integration of agriculture and veterinary medicine, improving the professional competence of grassroots veterinarians and livestock farmers has become particularly important. Agricultural veterinary education plays a crucial role in promoting sustainable agricultural development and cultivating a skilled veterinary workforce. However, current research on agricultural veterinary education is relatively scarce. Therefore, this paper explores the current state of research in this field and identifies its future trends, aiming to provide suggestions and references for research in agricultural veterinary education.MethodsThis study systematically reviewed the literature in this research field using text mining, knowledge graphs, and social network analysis, with a focus on the research trends and challenges in agricultural veterinary education. Through comparison of literature from different countries and regions, the differences and characteristics of agricultural veterinary education research in various countries were revealed. Particular attention was paid to educational content, research priorities, and international cooperation and knowledge exchange.ResultsResearch on agricultural veterinary education generally focuses on teaching methods, development strategies, and vocational training in agriculture. In China, the emphasis tends to be on aligning national policies with the broader agricultural development goals. On the other hand, other countries place more importance on practical educational approaches, particularly focusing on improving the skills of veterinarians and livestock farmers at the grassroots level. However, research on agricultural veterinary education at the secondary school level is still limited. Additionally, there is a growing need for more interdisciplinary research, especially in areas such as agricultural environmental veterinary education, which requires a deeper exploration.DiscussionFuture research should strengthen interdisciplinary collaboration to promote the comprehensive development of agricultural veterinary education. In particular, attention needs to be paid to education programs for grassroots veterinarians, and the curriculum should be improved by incorporating modern agrarian concepts such as environmental protection and circular agriculture. Furthermore, increasing practical components in agricultural veterinary education and enhancing teacher quality and overall educational standards will contribute to the advancement of agricultural veterinary education globally.